2019
DOI: 10.1016/j.bbmt.2018.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Conditioning Followed by Related and Unrelated Allografts for Hematologic Malignancies: Expanded Analysis and Long-Term Follow-Up

Abstract: Reduced-intensity conditioning (RIC) extends the curative potential of allogeneic hematopoietic cell transplantation (HCT) to patients with hematologic malignancies unable to withstand myeloablative conditioning. We prospectively analyzed the outcomes of 292 consecutive patients, median age 58 years (range, 19 to 75) with hematologic malignancies treated with a uniform RIC regimen of cyclophosphamide, fludarabine, and total body irradiation (200 cGy) with or without antithymocyte globulin and cyclosporine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Although the association between higher MMF dose and lower rates of acute GVHD has been previously reported by our group and others, there was a large interstudy variability on the approach used for MMF dosing for GVHD prophylaxis. [4][5][6]9,11,12,[24][25][26] While some transplant centers use fixed dose of MMF, 4,5,11,15,26 others use weight-based guided MMF dosing approach. 5,12,13 We previously showed that MMF dose of 3g/d vs. two prior studies that reported favorable effect of ≥30 mg/kg MMF dose on acute GVHD did not show increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the association between higher MMF dose and lower rates of acute GVHD has been previously reported by our group and others, there was a large interstudy variability on the approach used for MMF dosing for GVHD prophylaxis. [4][5][6]9,11,12,[24][25][26] While some transplant centers use fixed dose of MMF, 4,5,11,15,26 others use weight-based guided MMF dosing approach. 5,12,13 We previously showed that MMF dose of 3g/d vs. two prior studies that reported favorable effect of ≥30 mg/kg MMF dose on acute GVHD did not show increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…MMF was continued in patients who developed acute GVHD before day + 30 until 7 days after resolution of all GVHD symptoms. Supportive care and UCB graft selection criteria have been previously reported 2‐4,6,15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were adults with a diagnosis of hematological malignancy who received their first allogeneic HCT using RIC conditioning with cyclophosphamide/fludarabine/total body irradiation (Cy/Flu/TBI), a modification including low dose melphalan and post HCT Cy or Cy/Flu/TBI plus anti‐thymocyte globulin (ATG) for those without multidrug intensive chemotherapy in the preceding 3 months 1 …”
Section: Methodsmentioning
confidence: 99%
“…All were adults with a diagnosis of hematological malignancy who received their first allogeneic HCT using RIC conditioning with cyclophosphamide/fludarabine/ total body irradiation (Cy/Flu/TBI), a modification including low dose melphalan and post HCT Cy or Cy/Flu/TBI plus anti-thymocyte globulin (ATG) for those without multidrug intensive chemotherapy in the preceding 3 months. 1 We enumerated the complete and detailed transfusion data from day À10 to day 100 post HCT linked to the patient demographics including age, sex, race/ethnicity, and diagnosis. The donor and graft type, disease risk index (DRI), conditioning regimen, GvHD prophylaxis, Karnofsky performance score (KPS), and HCTcomorbidity index (HCT-CI) and extent of ABO match (ABO match/ minor mismatch / major mismatch / bidirectional) were considered as potential covariates that might influence blood product utilization.…”
Section: Patientsmentioning
confidence: 99%